In Hathor's image. - Callender, Vivienne G. (Charles University, Faculty of Arts in Prague, 2011)
This first volume contains a prosopographical register of the queens of Egypt from Dynasties I-VI and concentrates on providing an evidence-based assessment of the Egyptian queen within an historical setting. The temporal position of each woman, the monuments and titles she possessed, her familial links and any relevant iconography available are presented.